2017
DOI: 10.1615/intjmedmushrooms.v19.i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinase-1 (TIMP-1) and IL-23 Induced by Polysaccharide of the Black Hoof Medicinal Mushroom, Phellinus linteus (Agaricomycetes)

Abstract: Matrix metalloproteinase-9 (MMP-9) has diverse roles associated with cell growth, migration, invasion, and angiogenesis. Tissue inhibitor of metalloproteinase-1 (TIMP-1) is known to inhibit MMP-9 by complexing with it at a 1:1 ratio. Suppressing MMP-9 activity through the overexpression of TIMP-1 allows for regulation of tumor growth and metastasis by blocking invasion and angiogenesis in the tumor microenvironment. We found that TIMP-1 and interleukin (IL)-23 are induced in RAW264.7 macrophage cells, a cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, we assessed the role of CP-PGN if the cell line RAW264.7 established by Abelson leukemia virus infection carried more MyD88 themselves. 22 As shown in Figure 3(a) and (b), the MyD88 protein in CP-PGN–treated RAW264.7 cells was significantly lower than that of untreated control, inhibited by CP-PGN in a time- and dose-dependent manner. Furthermore, only CP-PGN significantly suppressed the MyD88 expression of RAW264.7 cells compared with MRSA and Pam3CSK4 (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 76%
“…Thus, we assessed the role of CP-PGN if the cell line RAW264.7 established by Abelson leukemia virus infection carried more MyD88 themselves. 22 As shown in Figure 3(a) and (b), the MyD88 protein in CP-PGN–treated RAW264.7 cells was significantly lower than that of untreated control, inhibited by CP-PGN in a time- and dose-dependent manner. Furthermore, only CP-PGN significantly suppressed the MyD88 expression of RAW264.7 cells compared with MRSA and Pam3CSK4 (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 76%
“…We previously demonstrated that polysaccharide of P. linteus [ 14 ] prevented tumor metastasis by inducing tissue inhibitor of metalloproteinase-1 (TIMP-1) and IL-23 in mice and RAW264.7 cells. We also reported that β-glucan from P. baumii induced flavin-containing monooxygenase (FMO) and activated NADPH oxidase, suggesting that β-glucan could enhance the detoxification of xenobiotics and macrophage-mediated phagocytosis, respectively [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%